Association Of Vitamin D And Magnesium With Insulin Sensitivity And Their Influence On Glycemic Control - Wan Nor Fazila Hafizan Wan Nik; Hani Ajrina Zulkeflee; Siti Nadirah Ab Rahim; Tuan Salwani Tuan Ismail (Baishideng Publishing Group Inc., 2024)
Indexed by WOS